2021
DOI: 10.3390/app11031199
|View full text |Cite
|
Sign up to set email alerts
|

3D Imaging of CRP and Ultrasonic Tomography to Detect Decay in a Living Adult Holm Oak (Quercus ilex L.) in Sardinia (Italy)

Abstract: A field-integrated methodology using 3D ultrasonic tomography supported by close range photogrammetry (CRP) has been developed and evaluated as a tool to detect the presence and patterns of decay forms in a living adult holm oak (Quercus ilex L.) in an urban green area of the city of Cagliari, Sardinia, Italy. Close range photogrammetry was used to compute a high resolution 3D model of the studied tree, texturized with natural colors. Moreover, following the implemented workflow process it was possible to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 46 publications
(66 reference statements)
1
15
0
Order By: Relevance
“…In a second stage, the images that were previously quality-checked (carefully selected) by the operator are aligned very precisely using bundle adjustment algorithms as well [41] and a sparce point cloud is generated. In the third step, this cloud is used as input in the computation of the final unstructured unified dense point cloud representing the high resolution 3D-model of the studied body, by means of Multi Video Stereo view (MVS) styled algorithms [3,4,6,9,25].…”
Section: Close Range Photogrammetrymentioning
confidence: 99%
See 3 more Smart Citations
“…In a second stage, the images that were previously quality-checked (carefully selected) by the operator are aligned very precisely using bundle adjustment algorithms as well [41] and a sparce point cloud is generated. In the third step, this cloud is used as input in the computation of the final unstructured unified dense point cloud representing the high resolution 3D-model of the studied body, by means of Multi Video Stereo view (MVS) styled algorithms [3,4,6,9,25].…”
Section: Close Range Photogrammetrymentioning
confidence: 99%
“…As a coupling agent, silicone snug sheets were used. From previous experimental ultrasonic applications [3,4,6,9,25], it was found that this kind of coupling agent is particularly suitable for use in porous media, such as natural materials. It optimises the transmissibility of the ultrasonic signal, filling the irregularities at the interface while avoiding soiling the material and interfering with it.…”
Section: Ultrasonic Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang and Khoshelham (2020) proposed a reconstruction method by combining structure from motion (SfM) photogrammetry and acoustic tomography to determine the internal wood quality. Puxeddu et al (2021) used close photogrammetry (CPR) and three-dimensional ultrasound to reconstruct the internal decay of a living adult holm oak. These methods can directly show the volume of wood defects and quantitatively understand the three-dimensional distribution of attenuation.…”
Section: Introductionmentioning
confidence: 99%